Analisis Kinerja Keuangan PT Anabatic Technologies Tbk Sebelum Dan Selama Pandemi Covid-19 Menggunakan Metode Economic Value Added (EVA) Periode 2017-2021 - Aida Rahmah Zakiah; Arif Afriady (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Abstract: The purpose of this research is to find out PT Anabatic Technologies financial performance Tbk before and during covid-19 pandemic using Economic Value Added (EVA) method. EVA method shows success in creating added value for shareholders and investors. This is a quantitative research with documentary data type using secondary data from the annual financial statements of PT Anabatic Technologies Tbk for the period 2017-2021 obtained on the website of PT Anabatic Technologies Tbk with documentation analysis techniques and analytical methods using Economic Value Added (EVA) method. From the research, the company’s EVA value before the covid-19 pandemic was positive, that the company can provide an appropriate return on the investment made by investors. Meanwhile, during Covid-19 pandemic, company's EVA value is negative, it means the company cannot return the appropriate investment to investors.